SOCIAL CULTURAL BENEFITS OF JATI BEACH TOURISM OBJECT IN TUAPEJAT VILLAGE, MENTAWAI ISLAND REGENCY, WEST SUMATERA PROVINCE - Naomi D Simamora; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Tourism activities at Jati Beach that involve the community directly will result in social and cultural changes in the community in Tuapejat Village. Changes that occur, both positive and negative, such as the formation of people's mindsets and habits and lifestyles towards a modern and consumptive direction will continue to take place over time so as to make Tuapejat Village more advanced, especially in tourism development that is more awake and sustainable. well preserved. This study aims to describe the Jati Beach tourist attraction and analyze the impact of tourism on the social and cultural life of the Tuapejat Village community. This study uses a qualitative method with a descriptive approach. The data collection techniques used were observation, documentation, and interviews with the Mentawai Islands Regency Youth and Sports Tourism Office, Tuapejat Village administrators and several Tuapejat Village communities. After conducting interviews with informants, the authors conclude that tourism activities in Jati Beach do not have a big impact on changes in the social and cultural life of the Tuapejat Village community due to the lack of community participation. Keywords : Impact, Social, Culture, Tourism